Should the IMF Become More Adaptive? - Clark, Ian. (Washington, D.C. : International Monetary Fund, 1996)
This paper addresses the question: Should the International Monetary Fund be making an even greater effort to adapt its objectives, priorities, rules, instruments, procedures, and resources to take account of changes in the global economic environment and in the needs of its members? It reviews the changes in the economic and geopolitical environment most relevant to the Fund and the ways the institution has adapted to date. It identifies the general factors that tend to inhibit adaptation in international institutions, and some of the specific factors that can facilitate adaptation in the case of the Fund. It concludes that the Fund should, indeed, be making even greater efforts to adapt, but that efforts in this regard should take account of the identified factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet